Meningkatkan Financial Management Behavior dan Investment Decision Making melalui Financial Knowledge, Attitude, dan Emotional Intelligence dengan Risk Perception - Satriadi, Dharma; Manurung, Adler Haymans; Sembel, Roy; Sutawidjaya, Ahmad Hidayat (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2023)
The objective of this study is to analyze the determinants of financial management behavior, specifically financial knowledge, financial attitude, and emotional intelligence on investment decision making with Risk Perception as a moderator. Using the Structural Equation Modeling – Partial Least Square analysis method, this study was conducted on a sample of 105 managers from Karawang International Industrial City. Financial Knowledge does not support Financial Management Behavior, Financial Attitude has a positive effect on Financial Management Behavior, Emotional Intelligence has a positive effect on Financial Management Behavior, Financial Knowledge does not support Investment Decision Making, Financial Attitude does not support Investment Decision Making, Emotional Intelligence has a positive effect on Investment Decision Making, Financial Management Behavior does not support Investment Decision Making, and Financial Attitude does not support Investment Decision Making. This research indicates the need to develop a financial education program that focuses on increasing financial knowledge and attitudes for managers, as well as paying attention to the development of emotional intelligence in order to improve the quality of their investment decision making.